Factors That Influence of Trabectome Surgery for Glaucoma Patients. Issue 9 (September 2017) - Tojo, Naoki; Abe, Shinya; Hayashi, Atsushi
Abstract : Background: The aim of this study was to investigate the factors that influence the outcome of trabectome surgery. Methods: This was a retrospective nonrandomized study. Seventy-eight glaucoma patients (86 eyes) who underwent trabectome surgeries and were followed up for more than 12 months were included. We classified the subtypes of glaucoma as: primary open-angle glaucoma (23 eyes), pseudo-exfoliation glaucoma (58 eyes), and secondary glaucoma (5 eyes). Forty-seven eyes underwent cataract and trabectome surgeries simultaneously, and 39 underwent only trabectome surgery. We evaluated the possible influencing factors including age, sex, glaucoma index, preoperative intraocular pressure (IOP), number of medications, visual field status, central corneal thickness, type of glaucoma and operation method (trabectome only or simultaneous cataract surgeries as well). Results: Trabectome surgeries significantly decreased the IOP from 23.0±6.7 to 12.5±3.0 mm Hg after 12 months ( P <0.001). The success rate at 12 months was 73.3%. The results showed that a low preoperative IOP, thin central corneal thickness, prior non–selective laser trabeculoplasty history, and simultaneous cataract and trabectome surgeries were factors that contributed to the success rate. Conclusions: The success rate of trabectome surgery was higher for low-IOP glaucoma than high-IOP glaucoma. Trabectome could be a useful treatment for low-IOP glaucoma.